The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1021/ac960638m
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wavelet Transforms to Experimental Spectra:  Smoothing, Denoising, and Data Set Compression

Abstract: Various methods have been proposed for smoothing and denoising data sets, but a distinction is seldom made between the two procedures. Here, we distinguish between them in the signal domain and its transformed domain. Smoothing removes components (of the transformed signal) occurring in the high end of the transformed domain regardless of amplitude. Denoising removes small-amplitude components occurring in the transformed domain regardless of position. Methods for smoothing and denoising are presented which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(149 citation statements)
references
References 12 publications
(17 reference statements)
1
146
0
Order By: Relevance
“…The triangle is likely to be the earliest peak model used (Dyson 1998) and is perhaps the simplest. It has been used as a peak model in a number of studies (Barclay and Bonner 1997;Stewart et al 2008). One definition for a triangle function is (Couch 1990),…”
Section: Peak Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The triangle is likely to be the earliest peak model used (Dyson 1998) and is perhaps the simplest. It has been used as a peak model in a number of studies (Barclay and Bonner 1997;Stewart et al 2008). One definition for a triangle function is (Couch 1990),…”
Section: Peak Modelsmentioning
confidence: 99%
“…Wavelet denoising strategies were also used (Ceballos et al 2008) on pattern recognition in CE. Similar wavelet based denoising strategies to those cited above have also been applied to liquid chromatography data (Barclay and Bonner 1997;Shao et al 2004), Raman spectroscopy (Hu et al 2007), mass spectrometry data (Barclay and Bonner 1997;Coombes et al 2005), as well as numerous other areas of research (Jagtiani et al 2008;Komsta 2009). The DWT is sufficient in many scenarios when removing high and low frequency noise from signals.…”
Section: Wavelet Transformation For Noise Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…For noise filtering of FT-ICR data, a discrete wavelet denoising operation [29] was performed using a 10-point Daubechies wavelet and a hard threshold function that zeroed the lowest 99.9% of points in the wavelet transformed data. This removed much of the noise, leaving signal peaks discernibly above the remaining baseline.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Closer inspection of the spectra showed that they consist largely of random noise as background to which a few fragment ion signals are superimposed. Consequently, we processed each spectrum to remove the noise using a wavelet denoising function [29] followed by a baseline correction. We then calculated arithmetic mean (Figure 7c) and standard deviation (Figure 7d) for the filtered fragment spectra and plotted them against decreasing ion activation attenuation on the x-axis, which corresponds to increasing kinetic energy of the precursor ions.…”
Section: Instrument Typementioning
confidence: 99%